Twelve-step Approach for Academic Development Planning in Academic Surgery: Climbing the Academic Uphill With Strong and Steady Steps. Issue 1 (6th March 2022) - Selvakumar, Sruthi; Ang, Darwin; Elkbuli, Adel
Abstract : Mini-abstract: Surgical trainees and young academic surgeons should understand the specifics of the career they are pursing, and surgeon mentors should enhance their leadership roles and support the recruitment and retainment of academic surgeons through effective academic career support and strategic planning. Utilizing academic development planning can serve as an essential tool as both mentors & mentees navigate different career choices towards achieving a successful and sustainable academic career advancement.